2018
DOI: 10.1182/bloodadvances.2018016006
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant GSK3β nuclear localization promotes AML growth and drug resistance

Abstract: Acute myeloid leukemia (AML) is a devastating disease with poor patient survival. As targetable mutations in AML are rare, novel oncogenic mechanisms are needed to define new therapeutic targets. We identified AML cells that exhibit an aberrant pool of nuclear glycogen synthase kinase 3β (GSK3β). This nuclear fraction drives AML growth and drug resistance. Nuclear, but not cytoplasmic, GSK3β enhances AML colony formation and AML growth in mouse models. Nuclear GSK3β drives AML partially by promoting nuclear lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…79 Recent data suggested that GSK-3β localization has clinical significance with worse patient survival and mediates drug resistance in both in vitro and in vivo. 80 GSK-3β is also upregulated in natural killer (NK) cells from AML patients compared to normal donors. 81 Same study showed that GSK-3β overexpression in NK cells impairs their ability to kill AML cells, while genetic or pharmacological GSK-3β inhibition enhances NK cell cytotoxic activity in human AML mouse models.…”
Section: Gbmmentioning
confidence: 99%
“…79 Recent data suggested that GSK-3β localization has clinical significance with worse patient survival and mediates drug resistance in both in vitro and in vivo. 80 GSK-3β is also upregulated in natural killer (NK) cells from AML patients compared to normal donors. 81 Same study showed that GSK-3β overexpression in NK cells impairs their ability to kill AML cells, while genetic or pharmacological GSK-3β inhibition enhances NK cell cytotoxic activity in human AML mouse models.…”
Section: Gbmmentioning
confidence: 99%
“…For the purposes of this review, it is important to point out that a fraction of GSK3 localizes to the nucleus of both healthy and cancer cells [21][22][23][24]. Consistently, some GSK3 substrates (e.g.…”
Section: Gsk3mentioning
confidence: 89%
“…However, there is also evidence showing that a high expression of GSK3β in the nucleus portends a poorer prognosis in renal cell carcinoma (RCC) [105,106] and in AML patients [23].…”
Section: Gsk3 and Its Impact On Rapamycin Sensitivity Of Cancer Cellsmentioning
confidence: 99%
“…GSK3β is mainly known as a cytoplasmic protein, but is also found in the nucleus and mitochondria (Bijur and Jope 2003). Recent studies have shown that nuclear localization of GSK3β is regulated by mTOR complex 1 (mTORC1) (Bautista et al 2018), and nuclear GSK3β facilitates acute myeloid leukemia (AML) cell growth and drug resistance (Ignatz-Hoover et al 2018). However, the regulation of nuclear GSK3β is not well defined.…”
Section: Discussionmentioning
confidence: 99%